LEXICAL AND SYNTACTIC AMBIGUITY IN THE VACCINE NEWS HEADLINES OF THE STAR - Chang Chui Shan; Bharathi Mutty, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Since the Covid-19 vaccination rollout, the news media has played an essential role in reporting the vaccine-related news to reduce the risk of getting and spreading the Covid-19 disease. However, people nowadays are preoccupied with busy schedules that they just glance at the news headlines and determine what they imply. If a word, phrase, or sentence in the headlines has more than one interpretation, they may misinterpret them and receive the wrong information. Therefore, this study aimed to investigate the lexical and syntactic ambiguity in the vaccines headlines of The Star news and to determine how these ambiguities affected the readers’ interpretation of the headlines. After collecting the headlines from The Star news, the definitions of the words and phrases were deduced using Oxford Learner’s Dictionary, while the sentence structures were identified using parsing. A questionnaire was also disseminated to the respondents to obtain different interpretations of the words or sentences. Next, a semi-structured interview was conducted with nine participants from three different educational backgrounds. The interviews were then transcribed and analysed thematically. The findings revealed that the lexical and syntactic ambiguity existed in the vaccine-related news headlines in The Star, with five lexical ambiguities and three syntactic ambiguities. Nonetheless, the participants were not affected by ambiguities because of the context and knowledge of the topic. The research study also posed a few limitations and gaps, where the other considerations and a larger sample of participants could be considered.